Reproductive Biology and Embryonic Diapause as a Survival Strategy for the East Asian Endemic Eagle Ray Aetobatus narutobiei - Yamaguchi, Atsuko; Furumitsu, Keisuke; Wyffels, Jennifer (Frontiers in Marine Science, 2021)
Batoids comprise five of the seven most threatened families of sharks and rays. The East Asian endemic Naru eagle ray Aetobatus narutobiei is a large bodied ray whose estuarine habitat overlaps with an economically valuable bivalve fishery. In response to decreased bivalve yields, the government initiated a predator control program and as a result, Naru eagle rays have faced intense and targeted fishing pressure during the last two decades. The long-term impacts of the predator control program on the population of rays and bivalves and their balance in the ecosystem are unknown because the life history of the Naru eagle ray has not been characterized. To begin to fill these critical knowledge gaps, the reproductive life history of the Naru eagle was described. Females mature at a larger size than males and require nearly twice as many years to reach maturity (DW50, 952.0 mm vs. 764.2 mm; Age50, 6.0 years vs. 3.5 years). Both males and females reproduce annually and their reproductive cycles are synchronized and seasonal. Females have a single ovary and paired uteri, are viviparous, and reproduce via matrotrophic histotrophy. Mating occurs in August and September and gestation lasts approximately 12 months including a 9.5-month diapause that begins soon after mating and ends in June of the following year, leaving 2.5 months for embryos to complete development. Fecundity ranged from 1 to 7 embryos per brood (n = 158, mean ± SD = 3.36 ± 1.26) and was positively correlated with female disc width (linear regression; F = 105.73, d.f. = 151, P < 0.05). Naru eagle rays are vulnerable to overfishing because of their low fecundity, long reproductive cycle and long time to reach sexual maturity. Obligate embryonic diapause during overwintering and seasonal migrations is a survival strategy that benefits the adults and neonates. This research is a valuable resource to help guide science-based management, conservation and protection of the endemic Asian A. narutobiei and its nursery areas.